Nursing and medical students’ views on their knowledge related to the Sustainable Development Goals – a mixed methods study at three Swedish universities - Maria Niemi; Helle Mölsted Alvesson; Daniel Helldén; Olivia Biermann; Eva Henje; Helena Nordenstedt; Carl Johan Sundberg; Tobias Alfvén (BMC Medical Education)
Abstract Background The challenges that the world faces to ensure good life for future generations are vast and complex. The United Nations Sustainable Development Goals (SDGs) aim to meet these challenges. A growing number of higher education institutions have integrated them within their curricula, but there are indications that health professional education has been lagging behind. Therefore, it is important to better understand the views of students in health professional education on the level and depth of their education on sustainable development. Methods This sequential exploratory mixed methods study was based on survey responses from N = 294 nursing (N = 137) and medical (N = 157) students of first and last semesters from three Swedish universities. From the full group of survey responders, 21 students participated in 5 focus group discussions (FGDs) and 9 individual interviews. The survey findings were summarized through descriptive statistics and the interviews and FGDs were analyzed by qualitative content analysis. Results The survey findings showed that most students (63%) perceived that they had not learned enough about the SDGs and Agenda 2030 during their education, or for the purposes of their future career. Most of the students (63%) also thought that Agenda 2030 and the SDGs should be a greater part of their education. The qualitative data gave a more in-depth understanding of the quantitative findings, forming two themes: The first theme revealed that the SDGs may be more relevant for health care practice than what the students initially thought, but that the education they had received was in most places superficial, or not tied to the SDGs. The second theme detailed what and how students wished to learn more about. Here, they called for a more in-depth understanding of how to promote equality, equity, inclusion and psychosocial aspects in health care. They also hoped for more knowledge about how to ensure a sustainable working life for themselves. Conclusions Nursing and medical students at three Swedish universities experience that they lack the knowledge necessary to face sustainability challenges they encounter in working life and give some suggestions about how this may be improved in future education.